2003
DOI: 10.1023/b:bile.0000004396.97796.0c
|View full text |Cite
|
Sign up to set email alerts
|

Focussed beam reflectance measurement (FBRM) monitoring of particle size and morphology in suspension cultures ofMorinda citrifoliaandCentaurea calcitrapa

Abstract: Laser light scattering technology, as applied in the Lasentec focussed beam reflectance measurement (FBRM) system, was used to characterise two morphologically dissimilar plant cell suspension cultures, Morinda citrifolia and Centaurea calcitrapa. Shake-flask suspensions were analysed in terms of biomass concentration and aggregate size/shape over the course of typical batch growth cycles. For the heavily aggregated C. calcitrapa, biomass levels [from 10-160 g fresh weight (fw) l(-1))] were linearly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The methods used to grow and morphologically analyse cultures of M. citrifolia and C. calcitrapa have been presented previously [16]. In brief, batch cultures of M. citrifolia and C. calcitrapa were grown in shake flasks.…”
Section: Plant Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used to grow and morphologically analyse cultures of M. citrifolia and C. calcitrapa have been presented previously [16]. In brief, batch cultures of M. citrifolia and C. calcitrapa were grown in shake flasks.…”
Section: Plant Cell Culturesmentioning
confidence: 99%
“…Jeffers et al [16] demonstrated that the biomass concentrations in plant cell cultures of both Centaurea calcitrapa (C. calcitrapa) and Morinda citrifolia (M. citrifolia) correlated well with total counts measured. C. calcitrapa grew as aggregates of 50-3,000 lm in size and cultures of 10-160 g FCW L -1 were linearly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…FBRM has been used to characterize a variety of particulate systems and its use in industry and academia is widespread, for example, crystallization, 13 polymerization, 14 wastewater treatment, 15 flocculation, 16 and plant cell suspensions. 17 The FBRM Model C35 system is equipped with a mechanical scraper, which can clear the optical window at a pre-defined time interval. This new feature allows the probe to be used in wet and sticky environments, without having to stop the process and clean the probe.…”
Section: Fbrm Methods Of Measurementmentioning
confidence: 99%
“…Although the probe has already been utilized for offline characterization of microbial [95][96][97][98] and plant cell systems [99][100][101], applications in cell culture processes are not yet reported. The latest version of the G400 FBRM system distributed by Mettler-Toledo is fully autoclavable and therefore allows the integration of this technology even in cell culture processes.…”
Section: Focused Beam Reflectance Measurement (Fbrm)mentioning
confidence: 99%